Commonwealth guide to trading with the Single European Market (Commonwealth Secretariat LondonGB, 1993)
Provides an introduction to the EC, explaining the removal of barriers to form the Single European Market, the implications for Commonwealth exporters and the broad details of the EC's trading rules with Commonwealth countries. Presents a products-based survey of the key factors governing access to the EC market. Lists important names, addresses and contact points of main organisations relevant to trading with Europe, together with some sources of useful publications.
DC